2009
DOI: 10.1007/978-1-4419-0213-9_63
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Fluorescence Microscopy of Mung Beanleaves

Abstract: Abstract:Recently, confocal microscope has become a routine technique and indispensable tool for cell biological studies and molecular investigations. The light emitted from the point out-of-focus is blocked by the pinhole and can not reach the detector, which is one of the critical features of the confocal microscope. In present studies, the probes acridine orange (AO) and rhodamine-123 were used to research stoma and mitochondria of mung bean leaves, respectively. The results indicated that the stomatal guar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, there may be significant limitations associated with 2-D leaf cross-section imaging (chloroplasts per cell cross-section or cross-section area) that hinder biological interpretation. The advantage of 3D imaging in plant structural and functional studies has been demonstrated in the literature (Armstrong et al, 2006;Chen and Liu, 2009;Omasa et al, 2009;Skaloud and Peksa, 2008;Wuyts et al, 2010). For example, in an earlier study on Opuntia ficus-indica, the number of chloroplasts and mitochondria per cell were addressed and a positive relationship between mitochondrial number per cell and leaf dark respiration rate was identified (Gomez-Casanovas et al, 2007).…”
Section: Correlation Between Leaf Structural Attributes and Functionamentioning
confidence: 99%
“…However, there may be significant limitations associated with 2-D leaf cross-section imaging (chloroplasts per cell cross-section or cross-section area) that hinder biological interpretation. The advantage of 3D imaging in plant structural and functional studies has been demonstrated in the literature (Armstrong et al, 2006;Chen and Liu, 2009;Omasa et al, 2009;Skaloud and Peksa, 2008;Wuyts et al, 2010). For example, in an earlier study on Opuntia ficus-indica, the number of chloroplasts and mitochondria per cell were addressed and a positive relationship between mitochondrial number per cell and leaf dark respiration rate was identified (Gomez-Casanovas et al, 2007).…”
Section: Correlation Between Leaf Structural Attributes and Functionamentioning
confidence: 99%